The effects of different desensitizer agents on shear bond strength of orthodontic brackets after home bleaching: an in vitro study - Gökmen Kurt; Yakup Üstün; Aslı Baysal; Nisa Gül Amuk (Istanbul University, 2018)
DOI: 10.26650/eor.2018.576Purpose The aim of this study was to test the null hypothesis that no difference exists between shear bond strength values of control and bleaching plus desensitizer applied groups. Materials and methods A hundred freshly extracted human premolar teeth were randomly divided into five groups. Group I served as the control group with no bleaching application, while only bleaching was achieved in Group II. Desensitizer containing potassium nitrate-fluoride and casein phosphopeptide amorphous calcium phosphate were applied in Groups III and IV, after bleaching respectively. A bleaching agent containing amorphous calcium phosphate was used in Group V. Shear bond strength tests were carried out using a universal testing machine (Instron Corp., Norwood, MA, USA). Remnant adhesive on the teeth and brackets was examined to score the adhesive remnant index. Kruskal-Wallis and Chi-Square tests were used for statistical analysis of the data. Results Statistically significant differences were found among the groups for shear bond strength values (p<.001). The shear bond strength of Group III (8.0±2.2 MPa) was significantly lower than the other groups (p<.05). The highest shear bond strength values were found for Group I (13.6±3.7 MPa) and Group IV (12.8±4.0 MPa). No statistically significant difference was observed between Group II (10.0±2.7 MPa) and Group V (10.8±2.9 MPa). The differences between adhesive remnant index scores of the groups were not statistically significant. Conclusion Casein phosphopeptide amorphous calcium phosphate gel application showed a similar shear bond strength value to the control group, while shear bond strength values decreased after using other desensitizers.